Cooperation and Integration Approach for Prevention of Adolescence Undesirable Pregnancy base on Collaborative Public Management - Chittanont, Manassawin; Naressenie, General Dr. Kasemchart; Thuvanuti, General Dr. Prasarnchoke (Journal for Developing the Social and Community, 2018)
The problem with teenage girls is still a major problem for Thai society from the past to the present. Especially, attitudes of teens about premature intercourse and pre-composition is normal in modern society. Although, technology and communication are boundless and reach closer to adolescents, but the teen's interest in contraception is very limited such as self-esteem awareness, perception of safe sex, including provides access to government agencies that provide assistance, it is also used by young women to prevent problems that may occur on their own. Therefore, when parents do not have time to introduce sexual hygiene to their children, the young teens learn about sex outside of the home rather than being guided by the home. These lead to the problem of adolescent girls in the context of Thai society is still high. Thus, this article is about the integration of knowledge and information on sexuality education from textbooks, books, etc. recommend also the involvement of family, community and society including the problem-solving approach requires cooperation from all parties, especially those close to the problem namely ; Family institution, Community Education Institutions as well as other related organizations collaborate to solve the problem continuously integrated.